Penafsiran Ayat-Ayat Keluarga Sakinah, Mawaddah, Wa Rahmah dalam Tafsir Al-Misbah dan Ibnu Katsir - Eka Prasetiawati (Nizham Jurnal Studi Keislaman, 2017)
The background of this research is a contrasting phenomenon of the realization of sakinah family in community life. The family is the smallest group in society, consisting of husbands, wives and children. It is the principle of forming a society. The majority of people assume that the factor of peace in family life is material, but many rich people who do not get peace at home so often the quarrels and discomfort. Problems that appear in the house can threaten the eternity of marriage even lead to divorce. It arises because the unfulfilled hope of each partner and mental, social and spiritual unpreparedness. Furthermore, researcher examined the verses of sakinah mawaddah wa rahmah family in contemporary and classical interpretation as a solution in realizing sakinah family today. In the hope, finding a relevant and even solute interpretation to deal with the current problem. For writers, it is useful to add insight into the mindset, attitude, and experience as an effort to improve the quality of learning, by understanding the character of sakinah, mawaddah, wa rahmah in the family. The formulation of problem in this research is (1) How is the view of Qur'an about sakinah family? (2) How to interpret the verses of sakinah family, mawaddah, wa rahmah in tafsir al-Misbah and Ibn Kathir? (3) How is the different interpretation of Quraish Shihab and Ibn Kathir in understanding the sakinah, mawaddah, wa rahmah verses? This research is a literature research which makes the interpretation of al-Misbah and Ibn Katsir as the main source of research. This research uses descriptive-analytic approach. The method uses comparative analysis, which is to compare contemporary and classical interpretations to know the results of interpretation and the differences in the field of exegesis. Another analysis using maudhu'i method is discuss the verses according to the appropriate theme with collecting and deep studying various aspects related to asbab al-nuzul, mufradat and interpretation of the verses.